The impact of communication regimes on group rationality: Experimental evidence - Lukas Meub; Till Proeger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
The performance of groups has been thoroughly investigated in experimental economics, showing that groups are overall more rational deciders than individuals. However, superior group performance in economic experiments has primarily been shown for face-toface decision making, which has ceased to be the prevalent form of communication in many IT-based organizations. To test the robustness of higher group rationality under conditions of virtual communication, we conduct a social learning experiment. We find that virtual communication leads to a substantial deterioration of group rationality for a judgmental task, while there is no effect for a purely intellective task. Further, we show that higher cognitive abilities of group members have no impact for the judgmental task, yet increase rationality for the intellective task. Our results have potential implications for the design of communication structures within decentralized organizations relying on virtual communication.
Keywords: C9; D8; 330; cognitive abilities; communication; group composition; group performance; laboratory experiment; methodology; social learning